THE CONCEPTUAL MODEL OF CORRECTION OF NEGATIVE MENTAL STATES AND PSYCHOSOMATIC DISORDERS IN PRESCHOOL CHILDREN BY MEANS OF BODY-ORIENTED THERAPY - Revutskaya, Irina (PSYCHOLOGICAL JOURNAL, 2018)
The article is devoted to negative mental states and psychosomatic disorders of preschool age children and means of their correction. The article examines the research of Russian and world scientists on the uniqueness of preschool age, its influence all subsequent development of man. Particular attention is given to mental states, at this age, which cause psychosomatic problems. The paradigm of bodily-oriented therapy of well-known scientists of the world is considered, according to which corrective measures to overcome this problem were developed. The techniques of work with negative mental states and psychosomatic disorders of preschool children are considered. The conceptual model of correction of negative mental states and psychosomatic disorders of preschool children is described, which includes the following structural components: physical diagnostics of negative mental states using “Child Mapping” for the detection and correction of psychosomatic problems in preschool children, corrective program for the elimination of negative psychic states and psychosomatic disorder in preschool children by means of body-oriented therapy and effectively - a dynamic structural component for determining the changes and changes depending on corrective measures. The formed principles of work of body-oriented therapy with children. The program of body-oriented therapy, consisting of techniques and techniques of execution, the algorithm of work in specific block diagrams and its phased use, is presented. The program complexes under the “Relaxation” and “Activation” directions are considered. The instruments of influence on the touching body are given and their classification is given: earth, water, air, wood, metal, fire, as well as the techniques and techniques described therein. Described negative mental states to which this or that type of touch is applied. The aforementioned parts of the body through which one can influence the negative mental states of preschool children.